UNASUR, Brazil, and the South American defence cooperation: A decade later - Vaz, Alcides Costa; Fuccille, Alexandre [UNESP]; Rezende, Lucas Pereira (Inst Brasileiro Relacoes Int, 2017)
UNASUR and its Defence Council (SADC) were created under a promising scenario of regional cooperation. Almost ten years later, a growing demand for regional cooperation arises, facing, however, low levels of political willingness from local governments. Through the lenses of structural and neoclassical realism, this paper suggests that the lack of support by governments, especially the Brazilian one, due to a change in how domestic ideas are developed, and a transformation in the regional balance of power, have contributed to these institutions' quick obsolescence.
Keywords: UNASUR; South American Defence Council; Defence Cooperation; Brazil; Neorealism; Neoclassical Realism